A Filter Paper Method for the Detection of Plasmodium falciparum Gametocytes by Reverse Transcription Polymerase Chain Reaction - Mlambo, Godfree; Vasquez, Yessika; LeBlanc, Ralph; Sullivan, David; Kumar, Nirbhay (The American journal of tropical medicine and hygiene, 2008)
Plasmodium falciparum gametocytes are obligate parasite sexual stages required for transmission of malaria from human hosts to the mosquito vector. Assessment of gametocyte carriers in the population is critical in understanding malaria transmission dynamics and in epidemiology studies. We applied a reverse transcription–polymerase chain reaction (RT-PCR)–based approach to detect pfs 25 transcripts from blood dried on different filter papers in the laboratory. The detection limit was 1–2 gametocytes/μL. We further validated this assay by analyzing RNA in 10 matched blood samples (liquid blood and blood spotted on filter papers) collected from subjects under field conditions in Zambia. These results thus establish feasibility of detection of Plasmodium falciparum gametocytes by RT-PCR method from dried blood on filter paper. This assay will greatly facilitate bulk analysis of gametocyte RNA transcripts on filter paper, especially in areas where collection and preservation of liquid blood is not feasible.